2021
DOI: 10.1590/0004-282x-anp-2020-0153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating subjective cognitive decline: a systematic review of tools available for evaluating cognitive complaints in Portuguese

Abstract: Background: Subjective cognitive decline (SCD) is a perception that is not objectively measured in screening tests. Although many tools are available for evaluating SCD, no single gold standard is available for classifying individuals as presenting SCD, in the Portuguese-speaking population. The aim of this study was to systematically review the literature for tools used to evaluate SCD in the Portuguese-speaking population. Methods: Four databases (Web of Science, SciELO, LILACS and MEDLINE) were primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In Brazil, there are few SCD questionnaires translated and adapted to our language and culture. In a systematic review, 25 Brazilian studies were identified, of which 19 used some type of standardized questionnaire 14 . In that review, four types of questionnaires were used in studies and only two had been properly validated.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, there are few SCD questionnaires translated and adapted to our language and culture. In a systematic review, 25 Brazilian studies were identified, of which 19 used some type of standardized questionnaire 14 . In that review, four types of questionnaires were used in studies and only two had been properly validated.…”
Section: Introductionmentioning
confidence: 99%